The Imaginary and the Reality in Arbitration in Public Procurement Comments to the Studies of the Centro de Análisis y Resolución de Conflictos de la Pontificia Universidad Católica del Perú and the Contraloría General de la República from Perú - Retamozo Linares, Alberto (2015)
This paper discusses the main variables, analysis and conclusions of the studies conducted by the Centro de Análisis y Resolución de Conflictos de la Pontificia Universidad Católica del Perú and the Contraloría General de la República from Peru. The author bases its investigation on the comparison between the two organisms; furthermore, he contrasts its conclusions andproposals with the data collected in the development of arbitration.